Lung function abnormalities among service members returning from Iraq or Afghanistan with respiratory complaints. (September 2016) - Holley, Aaron B.; Sobieszczyk, Michal; Perkins, Michael; Cohee, Brian M.; Costantoth, Camille B.; Mabe, Donovan L.; Liotta, Robert; Abraham, Joseph H.; Holley, Paul R.; Sherner, John
Abstract: Background: Service members deploying to Afghanistan (OEF) and Iraq (OIF) often return with respiratory symptoms. We sought to determine prevalence of lung function abnormalities following OEF/OIF. Methods: We identified OEF/OIF patients who had unexplained respiratory symptoms evaluated using lung function testing. Lung function data were summarized and analyzed for associations with demographic and deployment characteristics. Results: We found 267 patients with unexplained cough or dyspnea, lung function testing and a history of OEF/OIF deployment. All patients had basic spirometry performed and 82 had diffusion capacity for carbon dioxide (DLCO) measured. The median (IQR) number of deployments and total days deployed were 1 (1–2) and 352.0 (209–583), respectively. There were 83 (36.6%) patients with abnormal spirometry, 53 (63.9%) of whom had an abnormal FEV1 /FVC. Only one (1.2%) patient had an abnormal DLCO adjusted for alveolar volume. Of 104 patients who had post bronchodilator (BD) testing performed, six (5.8%) had a positive response by ATS criteria. We found no relationships between lung function and time in theater, deployment location, deployment frequency, or land based-deployment. Dyspnea and enlisted rank were associated with tobacco use and lower FEV1, and cough was associated with total number of deployments. Conclusions: Service members with respiratory complaints following OEF/OIF have a high prevalence of abnormalities on spirometry. Tobacco use, enlisted rank and total number of deployments were associated with symptoms or spirometric abnormalities. Highlights: We found one third of service members with post-deployment respiratory complaints have abnormal spirometry. Deployment characteristics (duration, frequency, location) were not associated with lung function abnormalities. Enlisted service members had lower values for spirometry and greater tobacco use. Tobacco use and abnormalities on spirometry were associated with respiratory complaints.